Intelligence in the modern world : John Dewey's philosophy - Dewey, John, 1859-1952; Ratner, Joseph, 1901-1979 (New York (N.Y.) : Modern library, 1939)
Selections from writings of John Dewey, with a 241 p. introduction by the editor.
The Meanings of Philosophy : Philosophy and Culture ; Philosophy and the Education of Man ; The Critical Function of Philosophy -- The Great Philosophic Separation : The Quest for Certainty ; The Historic Mission of Philosophy -- Philosophy And Science : The Modern Crisis ; Ancient and Modern Science Contrasted ; Philosophic Implications of Modern Science -- Science And The Future Of Society -- The Modes Of Societal Life : The Private and the Public ; Government and State ; State and Society ; Communication and Communal Living ; The Democratic Form -- The Individual In The New Society : The Individual in the Cultural Crisis ; The Economic Basis of the New Society -- Intelligence In Social Action : Classes, Groups and Masses ; The Class Struggle ; The Meaning and Office of Liberalism ; Socializing Intelligence -- Nationalism And Internationalism : Nationalism and Its Fruits ; Ethics and International Relations ; Force, Violence and Law -- International Law And The Security Of Nations : On International Cooperation ; On America's Responsibility ; Preconditions of the Security of Nations ; International Law and the War-System ; Editor's Note ; Sanctions and the Security of Nations -- Fundamentals Of The Educational Process : The Art of Education ; Learning and Doing ; The Training of Thinking ; Individuality and Freedom ; The Continuity of the Educational Process.
Donation in memory of Lionel V. Patenaude.
Supplemented by: A critical index, indexing all Dewey's ideas and explications of terms ... Also a supplementary analytic index ... (28, 8 l ; 29 cm.) published: Sharon, Mass. : Edward A. Post, 1960. Call no.: B945.D41 R17 Index.
Keywords: Dewey, John, -- 1859-1952.